A diquat-containing macrocyclic anion acceptor in pure water. Issue 57 (28th June 2019) - Lei, Ye; Shen, Libo; Liu, Ji-Ren; Jiao, Tianyu; Zhang, Yang; Zhang, Chi; Tong, Lu; Hong, Xin; Pan, Yuanjiang; Li, Hao
Abstract : A self-assembled diquat-containing tetracationic macrocycle is obtained in a high yield, which demonstrates its anion recognition ability in pure water. Abstract : By taking advantage of a newly developed self-assembly approach based on oxime condensation, we successfully obtained a tetracationic macrocycle bearing two diquats in acidic aqueous media in a high yield. The ring is able to accommodate HPO4 2− and HCO3 − in pure water.